Healthy Eating in Vulnerable Salvadorian Communities. - Fuster, Melissa. (2017)
Abstract: Food and nutrition security interventions in resource-poor settings more often than not emphasize food sufficiency over food quality. Globalization is driving changes in food environments, where cheaper, energy-dense, manufactured foods are widely available, and increasingly displacing traditional and often healthier food options. Availability and access are essential to food consumption, but food choices are an important factor in the process. The choice to eat healthy depends on different factors. This thesis focused on healthy eating from the perspective of border, resource-poor Salvadorian communities, through two Study Aims. Study Aim 1 compared perceived access to healthy diets (PAHD) and actual consumption using secondary information from 140 households in border, resource-poor communities in El Salvador. The data were collected by the Regional Program for Food and Nutrition Security in Central America (PRESANCA) from a sample of communities located in municipalities with high stunting rates and high vulnerability from climatic conditions (e.g. droughts and floods). Households were classified according to three different levels of PAHD (High, Moderate and Low) based on responses to an item from the food security measurement scale, and its follow-up frequency question. Diet quality was measured with the Household Dietary Quality Indicator (HDQI), an 18-component indicator based on the Salvadorian Dietary Guidelines constructed as part of this study. The sample presented overall low diet variety and HDQI scores. PAHD was positively associated with overall diet quality and variety, and higher intakes of animal products, fats, cholesterol, vitamin C, and sodium. High PAHD households had higher levels of women's education and household food security. Study Aim 2 was an ethnographic assessment of local definitions and perceptions concerning healthy eating in four resource-poor, border communities in El Salvador. The study included focus groups, key informant interviews, and observations of the food environment. The local definitions elicited through focus groups were compared to the national Salvadorian dietary guidelines recommendations, revealing areas of overlap (including the importance of dietary variety, fruits, and vegetables, among others) and omissions (mention of limiting sweets/candy, salt, sugar, and alcohol). Focus group participants expressed concerns over the origin of their foods and harmful chemicals in food. Barriers to healthy eating included economic and physical access to healthier food options and personal preference for convenience foods, among others. The results from this study highlight the importance of focusing on diet quality in contexts vulnerable to food insecurity. The consumption of healthy diets is affected by a conflict between nutrition knowledge and preference for often unhealthier, but convenient and more palatable options, which are also perceived as more prestigious. The findings can influence future nutrition and public health interventions targeted at improving the quality of the diet among populations in similar resource-poor communities in developing countries. Understanding factors associated with the consumption of a healthy diet in a Latin American country will also have the potential to inform culturally appropriate interventions for Hispanics living in the US, who often come from similar vulnerable communities, as those included in this study.; Thesis (Ph.D.)--Tufts University, 2013.; Submitted to the Dept. of Food Policy & Applied Nutrition.; Advisor: Odilia Bermudez.; Committee: Ellen Messer, and Robert Houser.; Keyword: Nutrition.